Women entrepreneurs in Southern Ethiopia: Capacity building programs for women empowerment and challenges in implementation. (4th May 2023) - Mamo, Yodit Abebe; Sisay, Abrha Mesele; Gilo, Beyeneche Yilma; Gebreselassie, Habtamu Gebremariam; Debisa, Mary Abera
ABSTRACT: This study evaluates the availability of capacity-building programs for women entrepreneurs and investigate the main challenges that women entrepreneurs face. 258 women entrepreneurs were randomly selected from six randomly selected zones in the SNNPR using a two-stage selection technique. Paper Assisted Personal Interview (PAPI) method was used to acquire quantitative data from women entrepreneurs. In addition, key informant interviews and focus group discussions with government officials and women entrepreneurs were conducted. Quantitative data were interpreted using inferential statistics such as proportion tests, pairwise proportion tests, and chi-square test, while qualitative data was analyzed using the thematic method. We found that training, marketplace, and cooperative services are relatively easily provided and implemented, while credit and market information are challenges for women entrepreneurs. Financial constraint is a main problem. Findings show that government and other bodies are working to strengthen the capacity of women entrepreneurs but that implementation is the weak link.